Randomized trials of adjuvant and neoadjuvant chemotherapy in bladder cancer - Dimopoulos, M.A.; Galani, E. (Seminars in Urologic Oncology, 2001)
Data of randomized studies of adjuvant and neoadjuvant chemotherapy for patients with muscle-invasive bladder cancer were reviewed. Four adjuvant studies have been published. The interpretation of their data is compromised primarily because of small patient numbers. Thus, a possible survival advantage cannot be documented, and significantly larger, prospective studies are needed. However, there is some evidence of improved disease-free survival for patients with non-organ-confined tumors treated with cisplatin-based combination chemotherapy. More data are available for neoadjuvant chemotherapy. The already published randomized studies, including a large trial of who was designed to detect a 10% survival benefit, do not indicate a significant advantage for neoadjuvant chemotherapy. Radical cystectomy remains the standard treatment to which other therapeutic modalities must be compared. Copyright © 2001 by W.B. Saunders Company.
Keywords: Adjuvant; Bladder cancer; Neoadjuvant chemotherapy